Integration of survival analysis in predicting customer churn risk to optimize life insurance redemption value formulation - Fachriz Effendy K; Risca Octaviyani Hutapea; Ardicha Appu Sianturi (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
The risk of voluntary policy surrender is a major threat to the liquidity and stability of life insurance companies' premium reserves. Conventional actuarial valuations, which assume a static depreciation rate, often fail to accurately mitigate this risk. This study aims to integrate a predictive analytics approach into actuarial mathematics to create a dynamic Surrender Value formula. Using 10,000 historical observations of financial customers as a proxy, the analysis was conducted using the Kaplan-Meier estimator and Cox Proportional Hazard (Cox PH) regression. The Kaplan-Meier estimation results show that the probability of policy survival experiences an exponential decay from 95.8% in the first year to 80.2% in the fifth year. Cox PH modeling confirms that entry age (hazard ratio = 1.048) and female gender (hazard ratio = 1.535) significantly increase the surrender risk, while active customer interaction (hazard ratio = 0.589) acts as a protective factor. The resulting cumulative individual hazard probabilities are then integrated as weighting constants into the surrender charge formula. This integration produces penalty recommendations that adapt to each policyholder's risk profile, providing more proportional and equitable liquidity protection for insurance company operations.